Achieving employee efficiency–flexibility ambidexterity. Issue 19 (27th October 2020) - Yu, Ting; Gudergan, Siegfried; Chen, Ching-Fu
Abstract: This study addresses a significant human resource management challenge, namely, the requirement that frontline service employees act ambidextrously to be efficient and flexible when delivering services. With a multilevel sample of 770 nurses in 48 units of one large hospital, this study demonstrates that individual characteristics – frontline service employee attitudes, perceptions of others' expectations of their behaviors, and self-efficacy – directly affect frontline employees' efficiency–flexibility ambidexterity. Work unit–level leadership partially moderates the impacts of these individual motivational factors. A significant positive relationship also is evident between employees' efficient–flexibility ambidexterity and their overall performance. This study is the first to clarify the motivational factors that drive frontline employees to behave in ways that enable them to meet efficiency and flexibility demands simultaneously.